(untitled) - Rycroft, David W. (Rome, 1995)
This book is included many parts: nature and distribution of clay soils, physical and chemical properties of clay soils, movement of water and salts in clay soils, drainage of clay soils, reclamation of salty clay soils, alternative strategies, case studies, economic analysis of the drainage of clay soils, environmental impact of land drainage and knowledge GAPS.
Keywords: Clay soils,Drainage,Đất sét,Thoát nước